Nutritional management in diabetic dogs: review - Massari, Catia Helena de Almeida Lima; Freires, Letícia Ribeiro; Costa, Hugo Leonardo Riani; Oyama, Silvia Maria Ribeiro; Saad, Flávia Maria de Oliveira Borges (Pubvet, 2021)
Diabetes mellitus (DM) is a metabolic disorder characterized by persistent hyperglycemia. Although most diabetic dogs have type 1 diabetes mellitus, type 2 diabetes mellitus can also especially afflict those who are obese. This study aims to investigate how nutritional management can help in the therapy of canine DM2 in relation to the modulation of the inflammatory process in obese dogs. A literature review was carried out using the following keywords: diabetes mellitus, insulin resistance, hyperglycemia, adipokine, adiponectin, inflammation, obesity, dogs. The present study concludes that nutritional management is an essential tool in the therapy of canine DM2 as controlling hyperglycemia can mitigate the consequences of the inflammatory process triggered in obese patients. Therefore, diets rich in protein and fiber are beneficial in increasing lean body mass and reducing postprandial hyperglycemia, generating animal welfare and favoring quality of life in canine patients.
Keywords: Diabetes mellitus; obesity; nutrition; inflammation; overweight